Effect of low- and high-dose levothyroxine on thyroid nodule volume: a crossover placebo-controlled trial - YAVUZ, DİLEK; KOÇ, MEHMET (BLACKWELL PUBLISHING LTD, 2002)
OBJECTIVE The efficacy and the effective dose of levothyroxine suppressive therapy in the treatment of benign thyroid nodules are controversial. In this study, we aimed to determine the response of solitary thyroid nodules to low- or high-level TSH suppression in a placebo-controlled, randomized crossover trial. DESIGN Forty-nine patients with solitary thyroid nodules on palpation were randomized to high-level and low- level TSH suppression groups. In each group, patients were further randomized to placebo and active levothyroxine subgroups. Patients in each subgroup were crossed over to placebo or active levothyroxine at the end of the first year and were then followed up for an additional year. METHODS TSH levels were suppressed to 0.4-0.6 mIU/ml and less than or equal to0.01 mIU/ ml in the low-level and high-level TSH suppression groups, respectively. Nodule volumes were measured at baseline and every 6 months after the desired level of TSH was reached if the patients were in the active levothyroxine treatment group or every 6 months if they were in the placebo group. RESULTS In high-level TSH suppression groups, nodule volume decreased significantly at the end of the active treatment periods (4.99 +/- 2.02 ml vs. 3.20 +/- 1.50 ml, P < 0.01, in Group 1; and 3.72 &PLUSMN; 1.79 ml to 2.05 &PLUSMN; 0.64 ml, P < 0.001, in Group 2). In the low-level TSH suppression groups, nodule volume also decreased significantly at the end of the active treatment periods (4.43 +/- 1.76 ml vs. 3.04 +/- 1.32, P < 0.05, in Group 3; and 3.59 &PLUSMN; 0.89 ml to 2.22 &PLUSMN; 0.59 ml, P < 0.01, in Group 4). Nodule volumes regained their original volumes during the placebo treatment periods. The percentage decline in clinically relevant nodule volume reduction (greater than or equal to50%) was similar in the low- level and high-level TSH suppression groups. CONCLUSION Low- and high-level TSH suppression were equally effective in reducing nodule volume and thus, considering the complications of high-level TSH suppression, low- level TSH suppression should be used if one considers levothyroxine suppressive therapy to reduce thyroid nodule size.
Keywords: THYROXINE SUPPRESSIVE THERAPY; PROSPECTIVE RANDOMIZED TRIAL; BENIGN SOLITARY; GOITER GROWTH; DOUBLE-BLIND; MANAGEMENT; ULTRASONOGRAPHY; THYROTROPIN; PREVALENCE; DISEASE